The Role of Strategic Leadership in Managing Conflict and Resistance to Change at APIPSU Medan Private High School - Nasution, Inom; Suwandi, Suwandi; Akhir, Muhammad; Nasution, Asrul; Nasution, Abdul Salam (Green Publisher Indonesia, 2022)
The purpose of this study is to explain the effect of conflict management strategies on teamwork performance. Conflict can happen to anyone and anywhere regardless of status, income and position. Someone who is not able to manage conflict will boomerang on his own performance and ultimately affect the company's performance. Thus, a conflict management strategy is needed as an effort to create good performance for individual employee performance and team performance. The results of the study prove that the hypothesis which states that conflict management strategies have a positive and significant effect on teamwork performance is accepted. This explains that conflict management strategies can contribute to teamwork performance through the ability of employees to accommodate ideas from co-workers, the ability to avoid differences of opinion by maintaining feelings and maintaining communication relationships, and collaborating on work methods. Suggestions for this research should be to improve conflict management strategies such as competing strategies at work by providing opportunities for other colleagues to use their expertise in making decisions and finding solutions to work completion.